The Pseudo-Clementine Recognitions as Early Christian Philosophy: Plato’s Presence in the Construction of a Christian Philosophical Way of Life - De Vos, Benjamin (Harvard theological review, 2025)
Recent scholarship has witnessed an increasing focus on the different (Greek, Latin, Syriac) versions of the Pseudo-Clementines as fourth- and fifth-century narratives, with each expressing its own unique rhetorical and religious-philosophical voice. In light of this, the different dynamics of the reception of ancient philosophy in the Pseudo-Clementine versions has garnered some moderate attention. In this contribution, I focus on the Latin version (Recognitions) and discuss the way in which the character of Peter and his students—former students of philosophy—systematically interpret the lives of the main character Clement and his parents within a framework of an original Christian-philosophical program (of ethics, physics, and epoptics). Additionally, Plato’s philosophy is key in this regard. I examine how a number of Platonic quotes and allusions—unique to the version of the Recognitions—play a fundamental role within the narrative arc of the Recognitions and within Peter’s discourse of (lived) Christian philosophy.